2017
DOI: 10.1037/adb0000279
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence based incentives plus parent training for adolescent alcohol and other substance misuse.

Abstract: The purpose of this study was to conduct a randomized test of clinic and home-based incentives plus parent training for adolescent problem alcohol use. Adolescents (N=75) with alcohol misuse, with or without other substance misuse were enrolled. All youth received individual Motivational Enhancement Therapy/Cognitive Behavior Therapy and weekly urine drug testing. The experimental condition (EXP) included Abstinence Incentives (ABI; clinic-based incentives for abstinence from all substances) plus weekly behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 35 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Contingency management (CM) is an approach that involves offering rewards contingent on engagement in substance use treatment and on evidence of abstinence. CM has now accumulated a robust evidence base in a variety of contexts, including smoking cessation, 26,27 heavy drinking 28 and drug misuse [29][30][31][32][33][34][35] and, in a fairly recent trial of a 12-week CM intervention, it was found to be clinically effective and cost-effective in reducing stimulant misuse in a cohort of patients with severe mental illness. 36 Furthermore, the National Institute for Health and Care Excellence (NICE) has recommended that it be adopted in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Contingency management (CM) is an approach that involves offering rewards contingent on engagement in substance use treatment and on evidence of abstinence. CM has now accumulated a robust evidence base in a variety of contexts, including smoking cessation, 26,27 heavy drinking 28 and drug misuse [29][30][31][32][33][34][35] and, in a fairly recent trial of a 12-week CM intervention, it was found to be clinically effective and cost-effective in reducing stimulant misuse in a cohort of patients with severe mental illness. 36 Furthermore, the National Institute for Health and Care Excellence (NICE) has recommended that it be adopted in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence continues to support multicomponent psychosocial treatments, as combinations of family-based therapy, cognitive behavioral therapy, motivational interviewing, and contingency management can be effectively utilized to treat adolescent SUDs [9,[18][19][20][21][22][23]. Combinations of motivational enhancement therapy (MET; described below in more detail in section 2) and CBT are well-established interventions for treating adolescent SUD [9,21], and other studies have found that contingency management, an intervention in which an individual is rewarded for positive behavior, can be an effective supplement to MET, CBT, and family-based therapies [19,20].…”
Section: C Multicomponent Psychosocial Therapymentioning
confidence: 99%
“…First, given the distribution of data and empirical precedent, alcohol consumption variables were coded as missing when <85% of the TLFB data were available. 40,41 When ≥85% of the TLFB data were available, the number of non-missing days were entered into the denominator to calculate alcohol use percentages. Second, participants who were missing any data included in the proposed models were subsequently removed from the main analyses.…”
Section: Discussionmentioning
confidence: 99%